2017
DOI: 10.1080/07391102.2017.1360209
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the structural, topological, and electronic properties of the functionalized Graphene nanosheets as potential Tegafur anticancer drug carriers using DFT method

Abstract: In the present work, we apply comprehensive theoretical calculations in order to study Tegafur drug adsorption on the nanostructured functionalized Graphene with hydroxyl, epoxide, carbonyl, and carboxyl groups in the water environment. The physical nature of Tegafur adsorption offers advantages in terms of easy desorption of anticancer molecule with no structural or electronic change of the adsorbed drug. By functionalization of Graphene nanosheet with a carbonyl group, a considerable increase on the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Their results have confirmed that the functionalized GNS with carboxyl group could be an appropriate couple for delivery of the Ampyra drug. The Tegafur drug adsorption on the functionalized GNS has been reported by Shahabi et al 22 According to their results, the functionalization GNS with a carbonyl group is a better absorber for the adsorption of Tegafur drug rather than other functionalized of graphene and the pristine graphene. Recently, we have also studied the adsorption and non‐bonded interaction between various drugs such as Syndros, 23 Resveratrol, 24 Alectinib, 25 Rubraca, 26 Curcumin, 27 Tyrphostin AG528, 28 Cytosine, 29 and Talzenna 30 over a variety of nanotubes.…”
Section: Introductionmentioning
confidence: 75%
“…Their results have confirmed that the functionalized GNS with carboxyl group could be an appropriate couple for delivery of the Ampyra drug. The Tegafur drug adsorption on the functionalized GNS has been reported by Shahabi et al 22 According to their results, the functionalization GNS with a carbonyl group is a better absorber for the adsorption of Tegafur drug rather than other functionalized of graphene and the pristine graphene. Recently, we have also studied the adsorption and non‐bonded interaction between various drugs such as Syndros, 23 Resveratrol, 24 Alectinib, 25 Rubraca, 26 Curcumin, 27 Tyrphostin AG528, 28 Cytosine, 29 and Talzenna 30 over a variety of nanotubes.…”
Section: Introductionmentioning
confidence: 75%
“…The positive values of ΔH and ΔG represent that the reaction process is endothermic and non-spontaneous. In contrast, the negative values of ΔH and ΔG indicate the reaction is an exothermic and spontaneous process [40].…”
Section: Bmsf-benz Adsorption On Al-cnt Nanotubementioning
confidence: 95%
“…The negative values of (ΔGSol) detect the spontaneous adsorption phenomenon, thus the adsorption of Hydroxychloroquine drug on these nanoparticles is more favorable because a spontaneous and appropriate adsorption behavior is clear. A substantial investigation for solvent effect on the complex which is directly related to the solubility of a complex is the dipole moment property, where the high value of the dipole moment refers to the higher reactivity, conductivity, and solubility in a polar media such as water [47]. The Dipole Moment (D.M) value of Hydroxychloroquine molecule in water was 11.94, which indicates a polar molecule, and after it was adsorbed on SiC-NT, Al-CNT, and Si-CNT, the dipole moments values which were obtained in gas phase, nearly doubled in the water phase.…”
Section: Aqueous Solution Effectmentioning
confidence: 99%